2023
DOI: 10.1002/cnr2.1802
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies for the treatment of squamous cell carcinoma: A literature review

Abstract: Background Squamous cell carcinoma (SCC) is a relatively common and heterogenous malignancy of different organs, such as the skin, esophagus, and lungs. Although most cases experience good survival with surgical methods, management of advanced types of the disease remains challenging. Several modalities, including different chemotherapy regimens and immunotherapies, have been investigated in this matter, among which Monoclonal antibodies (Mabs) are one of the most promising ones. Since the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 215 publications
0
0
0
Order By: Relevance
“…Therefore, Mabs are considered excellent options for treating SCC, especially for the advanced stages of the disease. Overall, two highly potent types of Mabs in SCC therapy are anti-EGFR Mabs and checkpoint inhibitors, especially cetuximab, nimotuzumab, and PD-1 inhibitors [66]. Precisely because there are several options, it is extremely important to thoroughly test the tumors at the beginning of the treatment, to make sure that the line proposed to the patient is the most suitable for his particularities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Mabs are considered excellent options for treating SCC, especially for the advanced stages of the disease. Overall, two highly potent types of Mabs in SCC therapy are anti-EGFR Mabs and checkpoint inhibitors, especially cetuximab, nimotuzumab, and PD-1 inhibitors [66]. Precisely because there are several options, it is extremely important to thoroughly test the tumors at the beginning of the treatment, to make sure that the line proposed to the patient is the most suitable for his particularities.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is an RTK that has an important role in cell physiology by regulating several signaling cascades involved in critical cellular functions such as proliferation, differentiation, survival and motility. However, when EGFR is mutated or overexpressed, it can trigger a neoplastic process ( 81 ).…”
Section: Egfr and Hnsccmentioning
confidence: 99%
“…CTX also activates proinflammatory and proapoptotic factors and inhibits repair of radiation-induced lesions, increasing the efficacy of strategies that combine EGFR-targeted agents and immune- or radiotherapy. CTX blocks invasion, angiogenesis and metastasis, which are protumorigenic roles of several signaling pathways associated with EGFR ( 81 , 107 ). By contrast, activating mutations in members of the RAS pathway may reduce the efficacy of CTX, leading to an improper ERK response and changes in transcription, cell fates and proliferation ( 108 ).…”
Section: Ctx Therapy and Head And Neck Carcinomamentioning
confidence: 99%
“…These studies have shown improved progression-free survival, overall survival, and objective response rates when bevacizumab is combined with standard chemotherapy or radiation therapy. Notably, the benefits may vary depending on patient selection, treatment regimen, and tumor characteristics (45).…”
Section: Therapeutic Targeting Of Vegf In Hnsccmentioning
confidence: 99%